Bike recommender system (BRS) - Mohd Zain, Muhammad Zabidi (2014)
This project is focused on the development of the Bike Recommender System. By applying Prototype Model to finish this project, it is dividing into several stages. For the first stage in the Prototype Model is initial requirement. In this stage the researcher collected all the data that related with the system. The information may come from informal interview, observation, journals and books. The second stage is design. At this stage the researcher will design the system based on customer requirement. The design is important part to satisfy the user requirement. After that is Prototype stage. At this stage, the researcher will design the prototype system based on the user need. After that the user will evaluate the system either the system meet their needs or not. Then, the researcher will review the user comment about the system and the researcher will make updating on the prototype and design. At the stage design, prototyping, customer evaluation and review and updating it will be done repeatedly to satisfy the user requirement. After user satisfied with the prototype, the system will be developing at the development stage. System testing is made after the development stage. After settled all the stage, the system will be maintained by the administrator of the system. This project has three objectives. The first objective is to analyze the data of the motorcycle that available in the market. Second objective is to design a Bike Recommender System and the last objective is to develop a working prototype Bike Recommender System. The scope of the project is targeted people that want to buy a motorcycle that available in Malaysia market. As the result, the system has two types of searching. User can search the motorcycle based on the requirement, usually related with their budget. Other type of searching is the user can continue to obtain the brand what they want. Under that brand, they can go through all the model design. For the future works, the system can be made more interesting and catchy. For the searching base on brand, the customer can see all the information directly, not only view the picture of the motorcycles.